Parallel plot visualization for novice users - Yusof, R.J.R.; Jomhari, N.; Zainuddin, R.; Baba, M.S.; Yusoff, Z.M. (2011)
Parallel Plot for novice users is discussed. A relational model of parallel coordinate was used for analysis based on an interface called PaCQ. The advantage and disadvantages of parallel plot is discussed. Although through literatures it wasfound that parallel plot does not score well in graphical perceptibility among users, results shows that novice users can interpret parallel plots relatively well. The GOMS analysis of tasks related to parallel plot also shows that the time taken to complete tasks related to the parallel plot is relatively reasonable, well below 10s. The user study among novice with three different levels of education shows no significant difference in the scores of interpreting the parallel plot.